Internet as a Learning Reference For Students - Hendri Irawan (Pena Cendekia Insani, 2022)
The internet is one of the technologies that help the development of information technology in this era. It is undeniable, the internet is increasingly accessible and used by many people, one of which is students such as university students. The method used in this research is interviews and literature review. Where the author interviewed several students related to the topic. Then look for references that are appropriate to the topic to analyze and understand the topic. The sample of this study were students. The conclusion of this study is that 98% of students often use the internet as a learning reference and this has increased since the pandemic. Various reasons make students inseparable from the internet while studying. This triggers students further away from books and encourages students to be dishonest in doing assignments.